Surge of Student Suicides Pushes Las Vegas Schools to Reopen - Green, Erica L (Brazilian Journal of Implantology and Health Sciences, 2021)
This text is a reproduction of the New York Times article “Surge of Student Suicides Pushes Las Vegas Schools to Reopen” and aims to disseminate the most relevant materials and information on the fight against COVID 19. https://www.nytimes.com/2021/01/24/us/politics/student-suicides-nevada-coronavirus.html